The manganese-salen compound EUK-134 and N-acetyl cysteine rescue from zinc- and paraquat-induced toxicity in rat polymorphonuclear leukocytes. (25th April 2015) - Kumar, Ashutosh; Shukla, Smriti; Chauhan, Amit Kumar; Singh, Deepali; Pandey, Haushila Prasad; Singh, Chetna
Highlights: Zinc and paraquat induce oxidative stress in rat polymorphs. Oxidative stress plays a critical role in metal and pesticides toxicity. Compromised antioxidant defense is implicated in zinc and paraquat toxicity. N-acetyl cysteine and EUK-134 mitigate zinc and paraquat-induced oxidative stress. Abstract: Oxidative stress is implicated in toxicant-induced inflammation leading to chronic diseases. Polymorphonuclear leukocytes (PMNs) offer the first line of defense against infection in the mammals and protect against inflammation-mediated pathological anomalies. Conversely, activated PMNs contribute to the oxidative stress-mediated damage and inflammation. The study aimed to investigate the status of oxidative stress and antioxidant defense system in the PMNs of rats treated with/without zinc (Zn) and/or paraquat (PQ) in the presence or absence of a synthetic superoxide dismutase/catalase mimetic, a manganese-salen compound-EUK-134 and/or a glutathione precursor, N-acetyl cysteine (NAC). While Zn and/or PQ elevated the total free radical generation, lipid peroxidation (LPO) and catalytic activity of myeloperoxidase (MPO), superoxide dismutase (SOD), glutathione peroxidase (GPx) and glutathione S-transferase alpha 4-4 (GSTA4-4), a pronounced decrease in reduced glutathione (GSH) and glutathione reductase (GR) activity was also observed. Zn and/or PQ augmented the expression of metallothionein-I and II and GSTA4-4. Pre-treatment of EUK-134 or NAC alone altered the level of total free radical generation, LPO, GSH content and catalytic activity of MPO, SOD, GR and GPx and the expression of metallothionein I and II towards normalcy. The alterations were more pronounced in the PMNs of rats treated with EUK-134 and NAC in combination. Catalytic activity/expression of GSTA4-4 remained unchanged in the PMNs of EUK-134 or NAC treated rats. The results demonstrate that EUK-134 and NAC protect PMNs from the toxic effects of Zn and PQ in rats and also suggest that metallothioneins I/II might contribute to antioxidant defense under GSH depleted conditions.